Global Company Handbook: An Analysis of the Financial Performance of the World's Leading 7,500 Companies. - Kinney, Michael R. (The Accounting Review, 1993)
Abstract Reviews the book "Global Company Handbook: An Analysis of the Financial Performance of the World's Leading 7,500 Companies," by Vinod B. Bavishi.